Temperature and low-stakes cognitive performance - Zhang, Xin; Chen, Xi; Zhang, Xiaobo (Institute of Labor Economics, 2023)
This paper offers one of the first evidence in a developing country context that transitory exposure to high temperatures may disrupt low-stakes cognitive activities across a range of age cohorts. By matching eight years of repeated cognitive tests among all the participants in a nationally representative longitudinal survey in China with weather data according to the exact time and geographic location of their assessment, we show that exposure to a temperature above 32 °C on the test date, relative to a moderate day within 22–24 °C, leads to a sizable decline in their math scores by 0.066 standard deviations (equivalent to 0.23 years of education). Also, the effect on the math test scores becomes more pronounced as people age, especially for males and the less educated. However, the test takers living in hotter regions or those with air conditioning installed on site are less vulnerable to extreme high temperatures, indicating the role of adaptation.